New deep-water Bryozoa from the Magellan Seamounts, tropical western Pacific, with a global review of bryozoans associated with ferromanganese crusts. (July 2022) - Grischenko, Andrei V.
Abstract: The sessile benthic fauna on ferromanganese (Fe-Mn) crusts is poorly known, with many groups of invertebrates still barely examined. Collections made during Yuzhmorgeologiya expeditions on RV Gelendzhik in October 2016 (YMG 6–16) and October 2020 (YMG 6–19) to the Magellan Seamounts, tropical western Pacific, have yielded two new species and a new genus of cheilostome bryozoans. These are Allantocallopora makarikhini sp. nov., obtained at Stn 14B135 from the Kotzebue Guyot, 17.3800°N, 153.0800°E, at 1505 m depth, and Melnikum magellanum gen. et sp. nov., collected at Stn 08D108 from the Govorov Guyot, 17.8984°N, 151.2415°E, at 2036 m depth. Colonies of these new species were attached to the surface of cobalt-rich Fe-Mn crusts, representing a rare example of detection of Bryozoa on Fe-Mn crusts in the deep-sea. A literature review revealed 23 reports documenting bryozoans on the surfaces of Fe-Mn crusts or the deposition of Fe-Mn oxides on the surface of bryozoan colonies, defined as ferrugination. Fe-Mn crust-associated Bryozoa have been found at 29 localities in ten regions of the world's oceans, in a depth range of 400–5850 m, with the majority of finds made in the central to southwestern Pacific. Most of these reports were based on preliminary data; they identified nine bryozoan taxa to the species level. Fe-Mn crust-associated bryozoans show low local species richness, up to four species per locality, and generally low abundance. Analyses of published data suggest that this apparent low richness might be due to the short history of investigations of crusts and strongly affected by the sampling method. Thorough inventories of Fe-Mn crust-associated bryozoans are urgently needed; bryozoans are a component of the sessile biota, which is sensitive and vulnerable to the proposed mining of Fe-Mn crusts as an important mineral resource in the deep sea.